The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1891/cn-2021-0021
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Participatory Action Research in the Nursing Field: A Scoping Review

Abstract: Participatory action research (PAR) is a method of inquiry that promotes a collaborative approach to knowledge creation. This article examined areas of research interest that included PAR methods, highlighting the areas of improvement that such approaches might offer to researchers and scientists in the nursing field. Among the 20 included studies, participatory concepts are more likely used to direct research design than to select participants. About two-thirds of the studies reviewed used PAR principles in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…However, in the case of mental health nursing, only half of the studies included users. This is also the case in other contexts, where there are still a small number of studies in which equal groups are formed between researchers and other stakeholders, not only in the design of the study but also in the selection of participants and data collection and analysis (Effendy et al, 2022;Wiles et al, 2022). From a methodological perspective, it is important to emphasize that although there are different approaches to action research (Rowell et al, 2017), the results of the review indicate that in the field of mental health nursing the commonly used method is Participatory Action Research.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, in the case of mental health nursing, only half of the studies included users. This is also the case in other contexts, where there are still a small number of studies in which equal groups are formed between researchers and other stakeholders, not only in the design of the study but also in the selection of participants and data collection and analysis (Effendy et al, 2022;Wiles et al, 2022). From a methodological perspective, it is important to emphasize that although there are different approaches to action research (Rowell et al, 2017), the results of the review indicate that in the field of mental health nursing the commonly used method is Participatory Action Research.…”
Section: Discussionmentioning
confidence: 94%
“…However, in the case of mental health nursing, only half of the studies included users. This is also the case in other contexts, where there are still a small number of studies in which equal groups are formed between researchers and other stakeholders, not only in the design of the study but also in the selection of participants and data collection and analysis (Effendy et al, 2022 ; Wiles et al, 2022 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In PubMed, there are over 10,000 references to CBPR, with a dramatic increase in the number of publications beginning in 2010. In a recent scoping review of participatory action research studies, Effendy et al (2022) identified 553 nursing studies. In addition, several nursing texts (De Chesnay, 2015; Pavlish & Pharris, 2012) focus on describing the foundations and detailing the processes of CBPR.…”
Section: Nursing Science and Research Methodsmentioning
confidence: 99%
“…It is useful for exploring the phenomenon under study because it makes it easier for participants to identify both the aspects to be improved and the most effective procedure to carry out such improvement (Casey et al, 2022). This research methodology has been introduced in recent years in the area of health sciences with successful results (Cordeiro & Soares, 2018) and, more specifically, in the nursing field (Effendy et al, 2022) as a pathway to implementing evidence‐based practice (Munten et al, 2010). In this sense, the PAR process in the nursing discipline enables a better understanding of the study phenomenon to design improvement strategies, implement changes and transform clinical practice (Bradbury et al, 2019) through a cyclical and continuous interaction of different stages such as action, reflection and evaluation (Rowell et al, 2017).…”
Section: Introductionmentioning
confidence: 99%